Comparison of 6 equations for estimating glomerular filtration rate in a Chinese benign hypertensive nephrosclerosis population. Issue 51 (23rd December 2021) - Ke, Guibao; Xie, Zhibin; Xiao, Jie; Zhang, Yamei; Hu, Yao; Li, Bohou; Jiang, Nan; Chen, Xueqin; Liu, Shuangxin; Shi, Wei
Abstract : Abstract: Equations to estimate glomerular filtration rate (eGFR) are useful for monitoring tje renal status of benign hypertensive nephrosclerosis (BHN). This study aimed to compare the applicability of 6 equations (Cockcroft-Gault [CG] adjusted for body surface area, original modification of diet in renal disease [MDRD], American abbreviated MDRD, Chinese modified MDRD, Chinese abbreviated MDRD, and Chronic Kidney Disease Epidemiology [CKD-EPI]) to estimate GFR in a Chinese BHN population. A total of 179 patients diagnosed with BHN were enrolled. The GFR estimated by each equation was compared to the reference GFR (rGFR) measured using the dual plasma sampling technetium-labeled diethylenetriaminepentaacetic acid method. The Chinese modified and Chinese abbreviated MDRD equations overestimated the rGFR, while the CG, CG adjusted for body surface area, original MDRD, American abbreviated MDRD, and CKD-EPI equations underestimated the rGFR. The difference in performance between estimated GFR (eGFR) based on the American abbreviated MDRD equation and the rGFR was not statistically significant ( P = .191), while differences in the others were statistically significant ( P < .05). Furthermore, the advantages in deviation, absolute deviation, deviation degree, precision, and accuracy were also significantly different from those of the other equations. Our findings suggest that eGFR based on the American abbreviated MDRD equation is suitable for the Chinese BHN population.